Strategi Penyelenggaraan Sistem Pengajaran Nasional (Analisis Teoretik terhadap Kurikulum, Pembelajaran, Evaluasi, dan Guru) - slamet hamid (Sosio e-Kons, 2019)
There have been several changes in the primary and secondary school curriculum system ever since Indonesia gained its independence. The changes could raise several questions due to the important and strategic role of the curriculum in achieving the objective of the national education system. This article discusses several issues related to the national instructional system, particularly about (1) the role of curriculum as a strategic means in school education, (2) the relevant objectives and contents of the curriculum, (3) the approaches in learning process and their implication to evaluation system, (4) evaluation as an educational medium as well as a feedback instrument, and (5) teachers.